Long-Term Supplementation of Royal Jelly (Raydel®) Improves Zebrafish Growth, Embryo Production and Survivability, Blood Lipid Profile and Functionality of Vital Organs: A 72-Weeks’ Consumption Study - Kyung-Hyun Cho; Hyo-Seon Nam; Ashutosh Bahuguna; Ji-Eun Kim (Pharmaceuticals, 2024)
Royal jelly is a honeybee product with substantial pharmacological and health promotional activities. Nevertheless, the health implications associated with the prolonged dietary supplementation of royal jelly have yet to be elucidated extensively. Herein, 72 weeks of dietary supplementation of royal jelly at 5% and 10% (w/w) were investigated to assess the impact on zebrafish survivability, body weight, liver, testis, ovary functionality, and blood lipid profile. The results revealed no adverse effect of 72 weeks of royal jelly supplementation on zebrafish survivability. Conversely, a noteworthy enhancement in the zebrafish body weight was observed in royal-jelly-supplemented zebrafish in a concentration-dependent manner [5% and 10% (w/w)]. Interestingly, female zebrafish were found to be more biased, with a significant 17% (p < 0.001) and 23% (p < 0.001) higher body weight enhancement after 72 weeks of consumption of 5% and 10% (w/w) royal jelly, compared to the male zebrafish. The histological outcome revealed no sign of hepatotoxicity; moreover, diminished reactive oxygen species (ROS) and apoptosis were observed in the hepatic tissue of the royal-jelly-supplemented group. Consistent with the histological outcomes, the liver function biomarkers, aspartate aminotransferase (AST) and alanine aminotransferase (ALT), exhibited a significant decrease of 1.9-fold (p = 0.006) and 1.4-fold (p = 0.003) in zebrafish supplemented with royal jelly compared to those on a normal diet (ND) and zebrafish given supplements. Also, no sign of ovary and testis-related toxicity was observed in the royal-jelly-supplemented group during the 72-week period. Furthermore, the 10% (w/w) royal-jelly-consuming zebrafish exhibited a notable 2.1-fold increase (p = 0.018) in egg-laying ability compared to the ND-supplemented zebrafish. The 10% (w/w) royal jelly supplementation also effectively maintained the blood lipid profile by curtailing serum triglycerides (TG) and elevating high-density lipoprotein cholesterol (HDL-C). Conclusively, royal jelly dietary supplementation for a prolonged time found royal jelly to be safe to consume, to efficiently improve hepatic function, reproduction, and sexual health, and to augment the serum HDL-C level.